2019
DOI: 10.1177/1526602818823557
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Clinical Outcomes of the Legflow Drug-Coated Balloon for the Treatment of Femoropopliteal Occlusions Registry

Abstract: To report the 1-year outcomes of the prospective Legflow drug-coated balloon (DCB) registry, which evaluated the safety and 12-month efficacy of the Legflow balloon in the treatment of femoropopliteal disease. Methods: The Legflow is a new generation of DCB that has a homogenous, stable surface coating incorporating 0.1-µm paclitaxel particles. From January 2014 to June 2016, 139 patients (mean age 67.1±10.8 years; 109 men) were enrolled at 4 European institutions. Seventy-nine (56.8%) patients had claudicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Twenty-six studies, 12 retrospective and 14 prospective, fulfilled the inclusion criteria (Table 1). 9,10,3558 A total of 2108 CLTI patients (mean age 71.3±4.4 years; 67% men) who were treated with DCB for peripheral atherosclerotic lesions were analyzed. Major risk factors were hypertension (91%, 1339/1478), diabetes (69%, 1138/1642), dyslipidemia (63%, 1101/1756), smoking (46%, 799/1754), coronary artery disease (41%, 602/1,468), and end-stage renal disease (26%, 389/1490).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-six studies, 12 retrospective and 14 prospective, fulfilled the inclusion criteria (Table 1). 9,10,3558 A total of 2108 CLTI patients (mean age 71.3±4.4 years; 67% men) who were treated with DCB for peripheral atherosclerotic lesions were analyzed. Major risk factors were hypertension (91%, 1339/1478), diabetes (69%, 1138/1642), dyslipidemia (63%, 1101/1756), smoking (46%, 799/1754), coronary artery disease (41%, 602/1,468), and end-stage renal disease (26%, 389/1490).…”
Section: Resultsmentioning
confidence: 99%
“…9,10,35,37,41,49,52,53,56,58 During 12-month follow-up in 11 studies, 9,35,37,40,41,49,50,53,55,56,58 82% (95% CI 76% to 87%; I 2 =73.7%) of the lesions remained patent, while the pooled TLR rate was 11% (95% CI 7% to 15%; I 2 =57.8%) in 12 studies. 9,10,35,4042,50,52,53,55,56,58 The pooled incidences of all-cause mortality in 12 studies 9,10,36,41,42,47,49,50,52,53,56,58 and major amputation in 13 studies 9,10,37,4042,47,49,50,52,53,56,58 at the end of follow-up were 8% (95% CI 5% to 13%; I 2 =75.9%) and 7% (95% CI 3% to 14%; I 2 =89.6%), respectively. Three studies 40,41,49 reported complete wound healing and ulcer reg...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations